The Aurignacian in the Carpathian Basin of Eastern Central Europe and its Proto-Aurignacian industry type - Yuri E. Demidenko; Демиденко Юрій; Demidenko Jurij; Petr Škrdla; Adrián Nemergut; Rats Adalbert; Rácz Béla; Рац Адальберт; Béres Sándor (Editura Cetatea De Scaun, 2021)
Abstract. The article represents our first article in a series planned by us, with some more following articles on Aurignacian, its industry types and possible industrial-chronological variability for a large region in the heart of Europe, the Carpathian Basin, Eastern Central Europe. Our study proposes to define four Aurignacian industry types: Proto-Aurignacian/Aurignacian 0; Early Aurignacian/Aurignacian I; Middle Aurignacian/Aurignacian II; Evolved Aurignacian with Gora Pufawska II-type microliths. The present article is particularly devoted to ProtoAurignacian sites and understanding its artefact complexity and variability. Certain attempts, based upon a number of artefact classification mistakes and their erroneous interpretations try to show that the Basin's assemblages in the Banat (south of the Carpathian Basin) allegedly represent a mixture of Proto-Aurignacian and Early Aurignacian features composing an "Aurignacian 0.5" industry; we demonstrate in detail the proper Proto-Aurignacian industrial status for all the Basin's sites and their finds, with some reservations for the Krems-Hundssteig site, Lower Austria. Moreover, the Carpathian Basin Proto-Aurignacian supports well the Aquitaine Aurignacian scheme. Some variability in the lithic assemblages is explained, in our view through the existence of various site types and their human activities, as it was established for the Ukrainian Transcarpathian record. Thus, finding some real industry variability endorses the classic French scheme.

Rezumat. Articolul de faţă este primul dintr-o serie dedicată Aurignacianului, tipurilor de industrii si a posibilelor variaţii cronologice pe cuprinsul unei arii largi din Europa: Bazinul Carpatic si Europa Centrală si de Est. Studiul nostru propune definirea a patru tipuri de industrii aurignaciene: Proto-Aurignacian/Aurignacian 0; Aurignacian timpuriu/Aurignacian I; Aurignacian Mijlociu/Aurignacian II; Aurignacian Evoluat cu microlite tip Gora Pufawska II. Articolul de faţă este dedicat cu precădere siturilor proto-aurignaciene si înţelegerii complexităţii si variabilităţii industriilor litice ale acestora. În unele publicaţii, bazate pe încadrări si interpretări eronate ale materialului litic, se încearcă demonstrarea amestecului elementelor proto-aurignaciene cu cele aurignaciene timpurii, rezultând asa-numitul "Aurignacian 0.5" în Banat (sudul Bazinului Carpatic); noi demonstrăm statutul proto-aurignacian clar al tuturor siturilor din Bazinul Carpatic, cu unele rezerve în ce priveste situl Krems-Hundssteig, din Austria Inferioară. Mai mult, Proto-Aurignacianul din Bazinul Carpatic se încadrează foarte bine în schema Acquitană a Aurignacianului. O anumită variabilitate este explicabilă prin existenţa a diferite tipuri de situri cu tipuri specifice de activităţi, după cum este cazul siturilor din Ucraina Transcarpatică. Astfel, existenţa unei variabilităţi la nivelul industriilor litice nu face decât să întărească viabilitatea modelului francez.
Keywords: Carpathian Basin; Early Upper Paleolithic; Aurignacian industry types; Proto-Aurignacian